Do people really want a simple tax system? Evidence on preferences towards income tax simplification - Sebastian Blesse; Florian Buhlmann; Philipp Doerrenberg (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
Using new survey and experimental data for a representative sample of the German population, we study preferences for tax simplification. The general wisdom seems to suggest that most tax systems are overly complex and that tax simplification is generally desirable. Consistent with this general wisdom, we find that more than 90% of our sample believe that the tax system needs to be simplified. However, there also are efficiency and equity arguments in support of a certain degree of tax complexity and it is puzzling why tax systems remain highly complex despite the conventional view in favor of more simplification. The main purpose of our study then is to investigate if the high support for tax simplification is driven by a lack of awareness about the trade-offs behind simple and complex tax systems. Our data show that the support for simplification decreases as we randomly provide economic arguments against simplification and as we ask respondents if the tax system should account for specific differences in living situations (such as costly care of elderly family members). Overall, our findings suggest that the high support for simpler taxes is to some extent driven by a lack of awareness about the implications of tax simplification.
Keywords: H2; D72; C9; 330; Tax Complexity; Preferences Towards Tax Simplification; Randomized Survey Experiment